What co-creation countermeasures can users take to stop the disorderly parking of dockless shared bikes?. (June 2022) - Wei, Wei; Jiang, Qianling; Gu, Chao
Abstract: Dockless shared bike (DBS) systems have rapidly developed in China in recent years, and have gradually expanded to all over the world. The DBS system also has become an important part of the urban slow traffic system. As a combination of mobile payment, the Internet of Things, and the sharing economy, the DBS system has brought many problems while developing rapidly. To solve these problems, many researchers suggest to introduce the theory of value co-creation. Based on theories related to value co-creation, this research uses open questionnaire surveys and principal component analysis to examine consumers' perceptions of themselves in value co-creation and their contribution to solving the problem of disorderly parking of shared bicycles. Academically, this article supplements consumers' perceptions in the field of value co-creation of shared bicycles. In practice, this article proposes countermeasures to solve the problem of disorderly parking of shared bicycles from the perspective of consumers.